2007
DOI: 10.1007/s11237-007-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-chemical DFT calculations of the molecular structure of N2O5 in the gas and solid phases

Abstract: By functional density quantum-chemical method (DFT/B3LYP using the 6-311++G(3df)) it has been shown that the molecular structures of N 2 O 5 with C s and C 2 symmetries are energetically equivalent. It follows from calculations of the vibrational frequencies that both structures are characterized by potential energy minima and correspond to stationary states of the N 2 O 5 molecule. It is proposed, on the basis of a comparison of the calculated and experimental vibrational spectra of N 2 O 5 , that dinitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…19,62 In our previous work the formation of ClNO was observed in AIMD molecular dynamics simulations of ONONO 2 adsorbed onto a thin film of water whose surface was struck by gaseous HCl. 63 Many electronic structure studies have been performed on N 2 O 5 and N 2 O 4 [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] providing information on equilibrium geometries, electronic and thermodynamic parameters, and spectroscopic properties. A summary of relevant DFT and non-DFT equilibrium geometries for N 2 O 5 can be found in Tables S1 and S2 of the ESI.…”
Section: Models and Methodologymentioning
confidence: 99%
“…19,62 In our previous work the formation of ClNO was observed in AIMD molecular dynamics simulations of ONONO 2 adsorbed onto a thin film of water whose surface was struck by gaseous HCl. 63 Many electronic structure studies have been performed on N 2 O 5 and N 2 O 4 [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] providing information on equilibrium geometries, electronic and thermodynamic parameters, and spectroscopic properties. A summary of relevant DFT and non-DFT equilibrium geometries for N 2 O 5 can be found in Tables S1 and S2 of the ESI.…”
Section: Models and Methodologymentioning
confidence: 99%
“…However, autoionization is not observed when deposited films containing only the symmetrical O 2 N-NO 2 structure are heated [7]. It can thus be assumed that the ionic form in the solid phase is formed during heating of the metastable molecular isomer with a substantial dipole moment, the presence of which and also the presence of charge polarization gives rise to the energy favorability for crystallization of the ionic structure in view of the crystal field energy [8]. Quantum-chemical calculations [9] showed that the molecular structure of the unsymmetrical O 2 NONO isomer with the trans configuration has the largest dipole moment (m » 2.6 D) (see Fig.…”
mentioning
confidence: 99%
“…In the present work, as in the previous report [8], we used the molecular orbital (MO) method in density functional theory (DFT) with the exchange-correlation functional B3LYP. In the 6-311++G(3df) basis set with optimization of the geometry a quantum-chemical calculation was made for all six known isomers with molecular structure N 2 O 4 .…”
mentioning
confidence: 99%